The continent of international law explaining agreement design - Koremenos, Barbara (Cambridge University Press, 2016)
"Every year, states negotiate, conclude, sign, and give effect to hundreds of new international agreements. In 2013, 500 separate agreements officially entered into force; an additional 248 agreements were modified. All told, a substantial body of international law was enacted or changed to adapt to the evolving needs of international cooperation. Adding these new pieces of international law to the body of already existing agreements, the total number of international agreements and agreement updates now in force approaches 200,000"--